Behavioral Biases on Generation Z's Investment Decisions in the Emerging Country’s Stock Market - Dwitya Aribawa; Bintang Ari Suwardi; Daniel Yudistya Wardhana (Petra International Journal of Business Studies, 2026)
Generation Z is a digital native generation that today is becoming more and more actively engaged as stock market users. They grow up in an era of information and technology where, although they have access to financial data, they remain vulnerable to psychological factors in making their investment decisions. This research therefore aims to investigate the role of behavioral biases, which are covered in this study, including overconfidence bias, herding bias, loss aversion bias, and anchoring bias, on the investment decisions of Gen Z in the stock market. A quantitative approach was used, applying multiple linear regression with Weighted Least Squares to address potential heteroscedasticity. These results show that overconfidence bias and loss aversion bias have a major impact on investment decisions of Generation Z; however, herding bias did not significantly affect this group, thus indicating Generation Z tends to make investment decisions on their own and is less likely to fall in line with the opinion of the majority or the market trend. This contrasts with the results of several previous studies and illustrates Generation Z’s more rational and financially savvy actions. Anchoring bias also has no significant impact at 5 percent, but it has a positive effect at the 10 percent significance level. These results indicate that Generation Z is adapted to new knowledge, reflection on the decisions they base on it, and less preoccupation with initial references.